2009
DOI: 10.1007/s00432-009-0625-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of a pretreatment hematologic profile in patients with head and neck cancer

Abstract: A pretreatment hematologic profile can be considered as a useful prognostic marker in patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 35 publications
3
73
0
1
Order By: Relevance
“…[137][138][139][140] The clinical features, associated malignancies, diagnostic studies, and treatment of paraneoplastic hematologic syndromes are listed in Table 4. 137,138,[140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156] eoSInopHIlIa Paraneoplastic eosinophilia represents a subset of secondary eosinophilia that appears due to tumor production of the eosinophil growth factors interleukin (IL)-3, IL-5, and GM-CSF. 137,157 By contrast, primary eosinophilia, a separate diagnosis encountered in hematology-oncology practices, often represents a clonal phenomenon caused directly by a hematologic neoplastic process.…”
Section: Paraneoplastic Hematologic Syndromesmentioning
confidence: 99%
“…[137][138][139][140] The clinical features, associated malignancies, diagnostic studies, and treatment of paraneoplastic hematologic syndromes are listed in Table 4. 137,138,[140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156] eoSInopHIlIa Paraneoplastic eosinophilia represents a subset of secondary eosinophilia that appears due to tumor production of the eosinophil growth factors interleukin (IL)-3, IL-5, and GM-CSF. 137,157 By contrast, primary eosinophilia, a separate diagnosis encountered in hematology-oncology practices, often represents a clonal phenomenon caused directly by a hematologic neoplastic process.…”
Section: Paraneoplastic Hematologic Syndromesmentioning
confidence: 99%
“…Hematologic abnormalities have been suggested as dismal prognosis signs of human cancers due to the implication of pathophysiologic responses to disseminated disease [1]. Pretreatment anemia is associated with shorter survival in numerous carcinoma patients, including lung carcinoma [2], cervical carcinoma [2,3], head and neck cancer [2,4], and esophageal cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, monocytosis has also been reported to indicate a worse prognosis in patients with adult T-cell leukemia/lymphoma 7 and head and neck cancers. 8 In patients with primary myelofibrosis, there is lack of information in relation to the development of monocytosis during the course of the disease. One study, however, has reported that the presence of absolute monocytosis at disease outset had a statistically significant, independent predictive value of inferior survival in younger patients with primary myelofibrosis.…”
mentioning
confidence: 99%